Liquidity and Profitability Analysis of the Financial Condition of PT. Campina Ice Cream Industry, Tbk - Sabilah, Tri Sal; Julkarnain, Julkarnain; Rangkuti, Lusi Elviani (EDUCTUM: Journal Research, 2025)
This study aims to evaluate the financial condition of PT. Campina Ice Cream Industry, Tbk through an analysis of liquidity and profitability ratios during the 2019–2023 period. This study uses a descriptive method with secondary data in the form of company financial reports taken from the Indonesia Stock Exchange. The results show that the company's liquidity condition is very good, with an average Current Ratio of 3748%, Quick Ratio 1151%, and Cash Ratio 683%, all of which exceed industry standards. Meanwhile, the company's profitability shows quite good results, with an average Gross Profit Margin (GPM) of 56.39%, Return on Assets (ROA) of 8.60%, and Return on Equity (ROE) of 9.77%. Despite a decline in 2020 due to the COVID-19 pandemic, the company's financial performance recovered significantly in the following years. Overall, PT. Campina Ice Cream Industry, Tbk is in a healthy financial condition and is able to maintain operational stability amidst external challenges such as fluctuations in raw material prices and market competition.